Preparing Students for Professional Communication: Developing Unique Communication Skills in Education (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Communication is a vital aspect of skill building, and it needs more the fluency of a language. It needs a thought process that is innovative in information processing and application based. Traditional educational systems don’t encourage strong skills for unique communication, furthеr weakened by a tendency of consuming ready-made material from easily available online courses. This article provides an approach to systematically develop an ability of self-unique expression instead of a copy-paste attitude.